Dynamics of Anti-HBc Serology During Anti-CD20 Therapy: Incidence, Timing, and Predictors of Anti-HBc Seroclearance in a Retrospective Cohort - Fatih Eren; Muhammed Abdurrahman Celik; Resul Akduman; Mete Yasar; Mehmet Refik Goktug; Gokhan Ocakoglu; Selim Gurel (Medicina, 2026)
Background and Objectives: Anti-hepatitis B core antibody (anti-HBc) is generally regarded as a lifelong serological marker of previous hepatitis B virus (HBV) infection. However, anti-HBc seroclearance has been increasingly reported in patients receiving anti-CD20 therapy, while its incidence, longitudinal serological dynamics, and clinical significance remain insufficiently characterized. In this study, we aimed to evaluate the incidence, timing, and predictors of anti-HBc seroclearance and investigate longitudinal changes in HBV serology in HBsAg-negative/anti-HBc-positive patients undergoing anti-CD20 therapy. Materials and Methods: This retrospective single-center cohort study included 230 HBsAg-negative/anti-HBc-positive adults who received anti-CD20 therapy between 2011 and 2025. Anti-HBc seroclearance was evaluated using Kaplan–Meier analysis and Cox proportional hazards regression. Longitudinal changes in anti-HBc and anti-HBs titers were assessed using linear mixed-effects models. Results: Confirmed anti-HBc seroclearance occurred in 38 of 230 patients (16.5%). Younger age (adjusted hazard ratio (aHR) 0.96, 95% confidence interval (CI) 0.93–0.98; p = 0.001), fewer anti-CD20 treatment cycles (aHR 0.90, 95% CI 0.83–0.99; p = 0.025), and mycophenolate mofetil therapy (aHR 2.52, 95% CI 1.14–5.56; p = 0.022) were independently associated with anti-HBc seroclearance. Anti-HBc titers progressively declined during follow-up, with a significantly steeper decline among patients receiving mycophenolate mofetil. HBV reactivation occurred in five of 230 patients (2.2%), including two who had developed anti-HBc seroclearance. HBsAg seroreversion occurred in all five patients. Conclusions: Anti-HBc seroclearance is a relatively frequent serological finding in HBsAg-negative/anti-HBc-positive patients receiving anti-CD20 therapy and is accompanied by progressive declines in anti-HBc titers. Despite seroclearance, HBV reactivation may still occur, indicating that anti-HBc loss should not be considered evidence of elimination of HBV-related immunological risk. These findings improve our understanding of HBV serological dynamics during anti-CD20 therapy and support maintaining current antiviral prophylaxis and virological monitoring strategies regardless of anti-HBc seroclearance.